PENGGUNAAN VIDEO PEMBELAJARAN DALAM PENINGKATAN KEMAMPUAN PEMAHAMAN PESERTA DIDIK TENTANG GERAKAN WUDHU TK RGM BESITANG - Safitri Br Rambe (CV. Arsy Persada Quality, 2024)
This study aims to improve students' learning outcomes on ablution material at Rgm Besitang Kindergarten, Besitang District, Langkat Regency, through the use of learning videos. This method was chosen because it can provide direct experience to children in understanding the steps of ablution practically. This study was conducted in two cycles, each of which included planning, implementation, observation, and reflection. The results of the observation showed a significant increase in students' understanding of ablution material. Before the application of the method using learning videos, the average score of students was at 65, while after the application of this method, the average score increased to 85. The conclusion of this study is that the method of using learning videos in improving students' understanding of ablution movements is very effective in improving student learning outcomes, and can be used as an alternative in the learning process at RGM BESITANG Kindergarten. It is hoped that the results of this study can be a reference for educators in designing more interesting and interactive learning strategies.